The Effect of Digital Literacy and Entrepreneurial Orientation on Business Performance of Ijuk Broom MSMEs in Tulungagung Regency - Ghina Nabilah; Hanif Mutiara Rohmah (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
Digitalization has become a key driving force in the transformation of MSME businesses. In the rapidly developing digital economy era, Micro, Small, and Medium Enterprises (MSMEs) face both challenges and opportunities to sustain their operations and improve competitiveness. This study aims to examine the effect of Digital Literacy and Entrepreneurial Orientation on Business Performance among Ijuk Broom MSMEs in Tulungagung Regency. The research population consists of 50 Ijuk Broom MSME entrepreneurs in Tulungagung. Data were collected through the distribution of questionnaires and analyzed using multiple linear regression techniques. The findings indicate that Digital Literacy has a positive and significant effect on Business Performance, suggesting that the ability to utilize digital technology effectively contributes to improved productivity, marketing, and operational efficiency. Entrepreneurial Orientation also shows a positive and significant effect on Business Performance, reflecting the importance of innovation, proactiveness, and risk-taking in business development. Furthermore, Digital Literacy and Entrepreneurial Orientation simultaneously have a positive and significant influence on Business Performance. These results highlight the importance of strengthening digital capabilities and entrepreneurial mindsets to enhance the performance and sustainability of MSMEs in the digital era.